Local and global prediction on stress-strain behavior of FRP-confined square concrete sections. (15th October 2019) - Jiang, Jiafei; Li, Pengda; Nisticò, Nicola
Abstract: The objective of this paper is to introduce a modified local-to-global methodology to understand the effect of fiber reinforced polymer (FRP) confinement on square concrete section. Traditionally, the effect of confinement on square sections has been evaluated through the so-called "arching effect" developed for steel and FRP-confined sections. FRP-confined square section was characterized by a non-uniform confinement stress field, which makes concrete strength strongly position dependent. This novel concept resulted in the "arching effect" being re-examined, which led to a methodology to evaluate the stress-strain behavior of concrete subject to arbitrary FRP confinement stress ratio at a local level. Because of the conception and realization of an innovative true-triaxial testing machine, by the first authors of this paper, research could be extended thus allowing for new test results that form the base of 1) an improved local constitutive relationship and 2) a modified approach for the evaluation of axial stress-strain behavior of an FRP confined square concrete column. The proposed approach has been validated by a set of experimental results of square columns and gave a new perspective on FRP confinement efficiency for square section.